Code Mixing Used by Yuki Kato in Bicara Cinta on Puella Id Youtube Channel - Anggelliya, Ni Putu Cahya; Matradewi, Ni Ketut Widhiarcani; Sosiowati, I Gusti Ayu Gde (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
Code-mixing gives an understanding of a mix of two languages or more by the multilingual. This study aims at defining the types and the factors causing the code-mixing used by Yuki Kato in a Youtube video. A mixed method was applied, with both qualitative and quantitative methods used in the study. The data is all of the words, phrases, or sentences that include the use of mixed codes in English and Indonesian Language, which was collected from one episode of Bicara Cinta on the PUELLA ID Youtube Channel. The code-mixing theory from Hoffman (1991) was used to analyze the data, including the types of code-mixing and the factors that caused the code-mixing. The analysis has identified 93 data on the use of code-mixing by Yuki Kato, including three types of code-mixing which are intra-sentential with 80 data found (86,02%), intra-lexical with 10 data found (10, 75%), and involving a change of pronunciation with 3 data found (3,23%). Six out of seven factors were applied in the code-mixing by Yuki Kato. The code-mixing produced by Yuki Kato is caused by several factors, those are talking about particular topic with 46 data found (49,46%), being emphatic about something with 35 data found (37,63%), intention of clarifying the speech content for the interlocutor with 7 data found (7,53%), repetition used for clarification with 2 data found (2,15%), interjection with 2 data found (2,15%), and quoting somebody else with only 1 data found (1,08%). There is no code-mixing caused by expressing a group identity. Keywords: Code-mixing, Codes, Youtube Channel